PENDAMPINGAN PROGRAM KAMPUS MENGAJAR ANGKATAN II TAHUN 2021 DI SDN 101 INPRES UJUNG KABUPATEN MAROS - Rahma Ashari (Politeknik Negeri Sriwijaya, 2021)
The Teaching Campus Program provides opportunities for students to participate and contribute to the world of education. In the implementation of the teaching campus at SDN 101 Inpres Ujung Maros Regency,5 students from various universities in Makassar carried out several program activities in addition to helping teaching and learning activities. These activities include the preparation of learning administration, making learning media, improving classes, structuring libraries, and using ICT in learning accompanied by Field Supervisors for five months. The implementation of the program in the target schools of the Teaching Campus is expected to provide knowledge and skills for students and teachers to improve the quality of education.